Assessing the effect of hypoxia on cardiac metabolism using hyperpolarized 13C magnetic resonance spectroscopy. (15th May 2019) - Le Page, Lydia M.; Rider, Oliver J.; Lewis, Andrew J.; Noden, Victoria; Kerr, Matthew; Giles, Lucia; Ambrose, Lucy J.A.; Ball, Vicky; Mansor, Latt; Heather, Lisa C.; Tyler, Damian J.
Abstract : Hypoxia plays a role in many diseases and can have a wide range of effects on cardiac metabolism depending on the extent of the hypoxic insult. Noninvasive imaging methods could shed valuable light on the metabolic effects of hypoxia on the heart in vivo . Hyperpolarized carbon‐13 magnetic resonance spectroscopy (HP 13 C MRS) in particular is an exciting technique for imaging metabolism that could provide such information. The aim of our work was, therefore, to establish whether hyperpolarized 13 C MRS can be used to assess the in vivo heart's metabolism of pyruvate in response to systemic acute and chronic hypoxic exposure. Groups of healthy male Wistar rats were exposed to either acute (30 minutes), 1 week or 3 weeks of hypoxia. In vivo MRS of hyperpolarized [1‐ 13 C] pyruvate was carried out along with assessments of physiological parameters and ejection fraction. Hematocrit was elevated after 1 week and 3 weeks of hypoxia. 30 minutes of hypoxia resulted in a significant reduction in pyruvate dehydrogenase (PDH) flux, whereas 1 or 3 weeks of hypoxia resulted in a PDH flux that was not different to normoxic animals. Conversion of hyperpolarized [1‐ 13 C] pyruvate into [1‐ 13 C] lactate was elevated following acute hypoxia, suggestive of enhanced anaerobic glycolysis. Elevated HP pyruvate to lactate conversion was also seen at the one week timepoint, in concert with an increase in lactate dehydrogenase (LDH) expression. Following three weeks of hypoxic exposure, cardiac metabolism of pyruvate was comparable with that observed in normoxia. We have successfully visualized the effects of systemic hypoxia on cardiac metabolism of pyruvate using hyperpolarized 13 C MRS, with differences observed following 30 minutes and 1 week of hypoxia. This demonstrates the potential of in vivo hyperpolarized 13 C MRS data for assessing the cardiometabolic effects of hypoxia in disease. Abstract : This study showed that hyperpolarized [1‐ 13 C] pyruvate can be used to non‐invasively visualize the cardiac metabolic changes that occur following systemic exposure to different lengths of hypoxia. Increased lactate production and decreased PDH flux was observed in the rat heart after 30 minutes of hypoxia. One week of hypoxic housing also caused increased lactate production, in line with increased ex vivo LDH expression. Three weeks of hypoxic housing was sufficient for metabolic adaptation to occur and thus no differences were observed between these animals and those housed in normoxia.